Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc053
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Steroid Chemistry and Biochemistry

Abstract: Steroids are a unique class of chemical compounds found throughout the animal and plant kingdom. This class includes sterols such as cholesterol and ergosterol, bile acids, and steroid hormones. Chemical research on steroids began with isolation and structure determination, and major research efforts focused on total synthesis and on the development of numerous reactions for modifying the steroid scaffold. Methods in microbial transformations of steroids were developed to produce large quantities of steroid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…After all, both progestogens, DHP and THP, are 20β-hydroxylated progestins; their only difference resides in the hydroxyl group at the 21 position (Matsuyama et al, 2002). Given that these progestogens are structurally similar and are produced from the same precursor, 17OHP (Brueggemeier and Li, 2010), it is reasonable to expect that the affinities of these progestogens for their receptor might result in strong competition. Due to their low or mild affinities to this MIH receptor, other nonprogestogen MIHs, such as corticosteroids, or nontypical MIHs, such as androgens and estrogen, have been hypothesized to be MIHs less frequently than progestogens (Thomas et al, 2002).…”
Section: -Progestogens As Mihsmentioning
confidence: 99%
“…After all, both progestogens, DHP and THP, are 20β-hydroxylated progestins; their only difference resides in the hydroxyl group at the 21 position (Matsuyama et al, 2002). Given that these progestogens are structurally similar and are produced from the same precursor, 17OHP (Brueggemeier and Li, 2010), it is reasonable to expect that the affinities of these progestogens for their receptor might result in strong competition. Due to their low or mild affinities to this MIH receptor, other nonprogestogen MIHs, such as corticosteroids, or nontypical MIHs, such as androgens and estrogen, have been hypothesized to be MIHs less frequently than progestogens (Thomas et al, 2002).…”
Section: -Progestogens As Mihsmentioning
confidence: 99%
“…Recent studies indicated that androgen effects might not be equal to the androgen receptor (AR) effects and ADT with antiandrogens [6] may only reduce the androgen biosynthesis or prevent androgen from binding to AR, with little effect on the AR expression [[7], [8], [9], [10], [11]]. Since more and more data indicated that AR, at the castration concentration (1–2 nM) of androgens, could also be transactivated by various growth factors, cytokines and kinases [[12], [13], [14], [15]], targeting the AR, instead of targeting androgens, may result in better efficacy to further suppress the PCa progression.…”
Section: Introductionmentioning
confidence: 99%